5x-3x=x+9

Simple and best practice solution for 5x-3x=x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3x=x+9 equation:


Simplifying
5x + -3x = x + 9

Combine like terms: 5x + -3x = 2x
2x = x + 9

Reorder the terms:
2x = 9 + x

Solving
2x = 9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
2x + -1x = 9 + x + -1x

Combine like terms: 2x + -1x = 1x
1x = 9 + x + -1x

Combine like terms: x + -1x = 0
1x = 9 + 0
1x = 9

Divide each side by '1'.
x = 9

Simplifying
x = 9

See similar equations:

| 8n=5n+39 | | 7.4=w-3.9 | | 33=7(w+7)-3w | | n-37=0 | | 150=v+113 | | sqrt(x+1)-sqrt(9-x)=sqrt(2x-12) | | -10g^2+13g-4=0 | | 2sin^2(4x)-1=0 | | -10g+13g-4=0 | | 3x+2*2x=21 | | 3.4=3p | | 9v=ir | | 3(x-8)=-9x+12 | | 10t-11=7t-5 | | 3.3x-11.26=5.9 | | -6x-2=(3x^2+1) | | 180=28x+(x*x) | | X(4X-8)=(4X+5)(x-2) | | 9+(9+x)+(9+.5(9+x))=9+(9+x)+(9+.5(9+x)) | | 3(x+5)=2(4x+10) | | 2(x-2)=60-(1-x) | | 14=0.8x | | 3x+3x+4x-30=180 | | 5y(2x-1)=y(x+2)+20 | | 2.9x-18.31=7.5 | | x^2+22x-40=0 | | 2.2x-15.18=3.3 | | 7m-4-2m=13 | | 3.5=3(4+.5r) | | X^4-8x^3+23x^2-28x+11=0 | | x-.3x=56000 | | x+.3x=56000 |

Equations solver categories